Evolution of public school inclusion policies in Brazil: between theoretical dilemmas and points of tension (Research, Society and Development, 2020)
This article aims to describe the evolution of public educational policies that ensure school inclusion in Brazil and promote the democratization of education. It is a descriptive study, in which the methodology of documentary and bibliographic research was adopted, based on theoretical references and official devices. At the interface of public policies, it was identified that they date back many years and were designed with the aim of meeting the demands of society in relation to differences. They have undergone changes that lead to the guarantee of rights for marginalized people at school and in society. In addition, they outline the valuation of differences, the promotion of dignity and the right to quality education for all citizens, with the State being the main responsible for providing conditions for their realization. The school inclusion policies propose a social and educational transformation, committed to the education of the citizen and the offer of an equitable education. However, it is worth mentioning that the State has not offered all the requirements to put into practice what is provided for in the legislation.